Midi controlled audio-DSP system - BOBIŃSKI, Piotr; BIELAWSKI, Bartosz (Archives of Acoustics, 2008)
The paper presents a MIDI controlled hardware station for digital audio signal processing. The system consists of an evaluation board ADSP-21364 EZ-KIT with the SHARC-21364 processor, and a MIDI to the SPI converter designed for the communication with a DSP processor. Information about hardware and protocols is included. The design of the converter device and the implemented software modules that enable to control the applications running on the DSP processor are described. Finally, two applications of the developed systems are introduced: synthesis of music with steering from a MIDI keyboard, and realization of recording with a control from a MIDI console.